Socio-demographic influence of food additives acceptance and avoidance among the Lebanese population: A cross-sectional study - Reham E. Kotb; Souheil Hallit; Farah Asmar; Melissa Fakhry; Chadia Haddad; Pascale Salameh; Samar Younes; Mohammed Hossni; Mohamad Abdelkhalik; Michelle Cherfane; Katia Iskandar (PLoS ONE, 2025)
Consumers’ exposure to food additives (FAs) through food consumption is becoming inevitable, triggering concerns about their safety. This study aims to evaluate the factors influencing food choices, the level of knowledge among Lebanese consumers about FAs, and the socio-demographic determinants of FAs acceptance and avoidance. A cross-sectional web-based study enrolling 601 participants was conducted online using the snowball technique. The questionnaire consisted of four parts, including the patient socio-demographic characteristics, knowledge about FAs’ definition and label content, the drivers of food choices, and FA acceptance and avoidance. Results showed varying levels of FAs knowledge across different age groups. Consumers indicated insufficient education about FAs (64.9%) and inadequate labeling (59.4%) are primary challenges in understanding food labels. Taste (75%) and price (62.2%) rather than FA content (29.3%) impacted food choices. Multivariate analysis showed that males were more likely to avoid FAs (β = 1.467, p = 0.016), as were university degree holders (β = 1.809, p = 0.012). Dieticians showed lower FA acceptance (β = −1.875, p = 0.031). The study highlights how socio-demographic factors and knowledge influence attitudes toward food adulteration, underscoring the need for targeted education, effective labeling policies, and further research on risk perception and behavioral change.